(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Lost circulation is one of the drilling operational problems. It refers to the total or partial loss of drilling fluid into highly permeable zones or natural or induced fractures. This problem is likely to occur when the hydrostatic head pressure of drilling fluid in the hole exceeds the formation pressure. Today, managing lost circulation remains a significant challenge to oilwell drilling operations because it may contribute to high non-productive time. It is imperative to note that the overbalance pressure situation also can cause the invasion of mud filtrate into production zones which will result in formation damage. To address these problems, an experimental investigation has been done on durian rind as an alternative fluid loss and lost circulation materials in water-based mud. Durian rind was selected as a mud loss control material because it contains close to 20% pectin which may complement the formation of high quality mat-like bridges across openings of the formation. The test involved the use of standard mud testing equipment and a lost circulation test cell. Durian rind powder was prepared by cleaning and cutting the durian rind into small pieces of 1 to 2 cm, and then dried them in an oven at 60Â°C for 48 hours before grinding into five different sizes from coarse to ultra-fine while Hydro-plug, the commercial lost circulation material was supplied by Scomi Energy. The fluid loss test was conducted using a standard low pressure filter press while the bridging test was carried out at 100 psi of pressure difference and ambient temperature using a lost circulation cell. Fine durian in the water-based mud gave the best fluid loss control compared to coarse durian rind, fine and coarse Hydro-plug. The experimental results also showed that at 15 lb/bbl (42.8 kg/m3) optimum concentration, coarse and intermediate durian rind have outperformed Hydro-plug by showing an excellent control of mud losses in 1 and 2 mm simulated fractures.